Teaching the concept of time: A steam-based program on computational thinking in science education - Kaan Bati; Mehmet Ikbal Yetişir; Ilke Çalişkan; Gökhan Güneş; Esma Gül Saçan (Cogent Education, 2018)
The aim of this research was to develop a STEAM-based program for teaching middle school students the concept of time to enhance their computational thinking skills. The proposed Time Teaching Program (TTP) consists of modules and activities on the definition of time, historical development of time measurement tools, universal time measurement system, space–time theory, and time as a fourth dimension. To determine the effectiveness of TTP and its effect on middle school students’ computational thinking skills, a mixed methodology was adopted in which both a quasi-experimental design including a pretest–posttest control group and an observational case study were used concurrently. The study group consisted of eighth-grade students from a public middle school in Turkey, selected according to the convenient sampling method. A computational thinking test was used to collect quantitative data, and observations and semi-structured interviews were utilized for the collection of qualitative data. According to the results of analyses, when the effects of the pretest scores were not considered, there was a significant difference (F.469, 1, R2 = .518) between the final test scores of the experimental and control groups in favor of the former. Based on these findings, it can be stated that the proposed STEAM-based program significantly improves the computational thinking skills of eighth-grade middle school students.